Demi Iman, Kehormatan, dan Harga Diri: Menelaah Kasus Bunuh Diri dalam 2Mak 14:37-46 - Jarot Hadianto (Jurnal Orientasi Baru, 2011)
A horrifying story of suicide is found in 2Macc 14:37-46. Surprisingly, the act isnot condemned; it is even highly praised. Can it be assumed then that the Bibleapproves suicide acts? To answer that question, we need to study the passagecarefully and compare it to other suicide stories that can be found in the OldTestament and Deuterocanonical books. Since the passage is considered as a storyof martyrdom, we need to consider also the Bible and Jewish traditions point ofview on martyrdom. There are many varying points of view that demand cautionwhen drawing conclusions on this controversial issue, by weighing in the contextof the story, political forces that influence the writing of the story, moral aspectsand avoiding literal interpretation of the Bible.